THE ROLE OF BAITUL MAAL WA TAMWIL IN ALLEVIATING POVERTY IN CIANJUR REGENCY, WEST JAVA - Reksa Jayengsari; Uus Ahmad Husaeni (Univeristas Islam Bandung, 2021)
This study aims to analyze the role of BMT in poverty alleviation in the Cianjur Regency. The research method used quantitative data collection using a questionnaire from 100 BMT members and data analysis techniques using multiple linear regression analysis. This article concludes that the poverty alleviation variable proxied by the income variable of BMT members is influenced by the real sector driving variable (providing financing) (t count 1.747, sig 0.045), business education to the community (t count 2.324, sig 0.006), Fund utilization Baitul Maal (t count 3,515, sig 0,000) and work motivation of members (t count 2,599, sig 0,000). Meanwhile, the variable of micro business empowerment/business assistance did not significantly affect the income of BMT members (t count -0.621, sig 0.536). Meanwhile, the R Square result is 0.643, which means that BMT members' variable income is influenced by the real sector driving variables, business education, fund utilization, work motivation, and business empowerment by 64.3 percent. In comparison, the remaining 35.7 percent is influenced by other variables. Thus, the conclusion of this study is members' perceptions of the existence and role of BMT in increasing community income to reduce poverty levels due to activities that are social, educational, and increase work motivation.